The Homegrown Downtown: Redevelopment in Asheville, North Carolina. (May 2017) - Strom, Elizabeth; Kerstein, Robert
The successful transformation of Asheville's downtown from desolate to vibrant is noteworthy. This article shows how successful redevelopment coalitions have shaped the downtown, with focus on the post-1980 period. In recent decades, public-sector officials and private investors have collaborated to create a downtown rooted in an architecturally significant historic built environment and based on independent business. Those most active have often crossed business, creative, and philanthropic sectors in ways we describe as "social entrepreneurial." The Asheville downtown coalition differs from the progrowth as well as the populist (progressive) regimes identified in other literature, but offers insights into downtown development efforts as urban governance becomes more fragmented and city development policy more focused on tourism and consumption.